Armenia : Poverty Update Using Revised Poverty Lines - World Bank (World Bank, 2012)
This study has two objectives, the first of which is to revise the national poverty lines of Armenia. The Government of Armenia expressed its desire for revised poverty lines that more accurately reflect the current consumption and expenditure patterns of the population. The work was jointly undertaken by the client counterparts and the World Bank. The second objective of this study is to assess the changes in poverty incidence in the aftermath of the global recession. This note updates the poverty numbers using the full dataset from the 2009 Integrated Living Conditions Survey (ILCS). It estimates how much poverty incidence increased during the crisis, and draws implications for mitigation measures. All poverty indices increased during the crisis and continued to worsen during the macroeconomic recovery.